Effectiveness of professional learning communities in developing electronic evaluation skills for mathematics and science teachers in the Sultanate of Oman - Al-Shidi, Khalid Juma; Qaddame, Mohamed; Shahada, Fwaze (Journal of Educational and Psychological Sciences, 2022)
The study aimed to explore the effectiveness of professional learning communities in developing electronic evaluation skills for a sample of mathematics and science teachers in the schools of the Sultanate of Oman. In order to achieve the objectives of the study, the experimental approach based on quasi-experimental approach was used for one group, and a teaching performance observation card was applied before and after. The electronic calendar skills consist of three areas: Skills of preparing questions and assignments using Google form/ live worksheet, skills of correcting questions and assignments using Google form/ live worksheet, skills of preparing activities and projects using Google form/ live worksheet/ Wizer.me, the study sample consisted of (25) teachers who were randomly selected from five intentional schools, The results of the study showed that there is an effectiveness of the post-performance in the overall performance of the electronic assessment skills of mathematics and science teachers and Earning rate of (62%) according to McGuigan’s earning rate. In light of the results, the study recommended several recommendations, the most important of which are: preparing training courses for mathematics and science teachers on using the Google Form/Live worksheet, preparing a question bank for mathematics and science subjects and including it in the educational platform using Google Form/Live worksheet, and training mathematics and science teachers on using the Live Worksheet in preparing projects and activities.